Orbitally-induced paleoceanographic changes in subtropical South Atlantic for the global climate over the last 800,000 years - Ballalai, João Marcelo (2023)
Anthropogenic greenhouse gas emissions significantly altered the Earth's climate system, particularly in recent decades. This increased atmospheric CO2 and global warming have been associated with the slowdown in the Atlantic Meridional Overturning Circulation (AMOC). The AMOC regulates climate by distributing heat and carbon throughout the Atlantic, maintaining the inter-hemispheric energy balance with the Intertropical Convergence Zone (ITCZ) and global atmospheric patterns. The wind-driven South Atlantic Subtropical Gyre (SASG), part of the upper limb of the AMOC, transports heat from the subtropics to the North Atlantic. Long-term climate changes are driven by cyclic oscillations in Earth's orbit, resulting in latitudinal and seasonal variations in incoming insolation. To fully comprehend the natural behavior and limitations of the AMOC, it is crucial to examine its dynamics on an orbital scale, considering surface and deep-water perspectives across different climates during the Late Pleistocene. This thesis focuses on the controls that orbital forcing exercises on paleoceanographic processes in the subtropical South Atlantic over the last 800 ka and their implications for global climate. By analyzing oxygen ( 18O) and carbon ( 13C) stable isotopes from benthic and planktic foraminiferal species from sediment cores GL-854 (25°12′S, 42°37′W) and MD08-3167 (23°18.91′S, 12°22.61′E), as well as Mg/Ca ratio of planktic species from core MD08-3167, this thesis aims to uncover the intricate relationship between AMOC modes and the set of different climates. The proposed framework provides a comprehensive understanding of deep-water and ocean-atmospheric processes, as well as of controlling mechanisms of the Benguela Upwelling System (BUS), on the orbital scale and their impacts on the global climate. Chapters 1, 2, and 3 are dedicated to the thesis's introduction, objectives, methods, and results. Chapter 4 investigates the deep-water circulation dynamic in the South Atlantic over the last 770 ka, based on the benthic foraminifera δ 13C record from core GL-854. This record is compared to published 13C data from the eastern South Atlantic to examine the zonal 13C gradient variability (∆13Cw-e) of North Atlantic Deep Water (NADW). It is proposed that AMOC oscillated between four modes controlled by orbitally-triggered variations in Antarctic sea ice extent. The orbital forcing is then propagated toward subtropical regions through controls over the deep-water formation. The proposed framework connects sea-ice and ocean-atmosphere dynamics to deep-water geometry within the South Atlantic basin, contributing to modulating the climate during the Late Pleistocene. Chapter 5 focuses on understanding the long-term variability of the BUS over the last 365 ka, based on the reconstruction of upper ocean stratification using the  18O gradient between planktic foraminifera species Globigerina bulloides and G. inflata (∆ 18O). Precessionally-paced stratification decrease is associated with the intensification and offshore expansion of the upwelling cell during austral summer insolation maxima. It is proposed that intensified deep-water formation in the North Atlantic during positive precession promotes intensified inter-hemispheric heat transfer, resulting in a northward shift of the SASG and enhanced the upwelling at BUS. A robust link is established between the upwelling intensification, the AMOC intensity, global atmospheric patterns, and a decrease in atmospheric CO2 during positive precession. Chapter 6 presents the protocol for performing Mg/Ca measurements in foraminifera samples using an ICP-MS performed at IFREMER. The protocol was applied to Globorotalia inflata specimens from core MD08-3167 to reconstruct thermocline temperature at the BUS over the last 365 ka. External reproducibility attests to accurate and precise results, allowing the continuous robust reconstruction of the Mg/Cabased thermocline temperatures. This record contributes to a better understanding of past oceanographic and climatic variability in the BUS and its implications for the carbon cycle. By combining surface and deep-water perspectives, studying ocean-atmospheric dynamics and the carbon cycle, we have gained insight into feedback mechanisms associated with AMOC variability, with important implications for atmospheric CO2.